'To kill an albatross is unlucky': maritime animals as symbols of freedom on Finnish windjammers in the 1930s. (2nd July 2020) - Mäenpää, Sari
ABSTRACT: This article explores encounters between wild maritime animals and humans on Finnish deep-sea sailing ships in the early twentieth century. At that time, sailing ships were disappearing from the world's oceans, and the deep-sea sailors of the 1930s romanticised themselves as representing the last wild and free adventurers in the world. Maritime animals played a central role in this romanticisation, and the encounters with them therefore came to be highly ritualised. Drawing on sailmaker Winifred Lloyd's (1897–1940) diaries and other maritime accounts of that time which contain rich textual and visual evidence, this article argues that the albatross embodied the glamour of maritime adventures, the heroic meeting between sailors and the ocean, and the sailing ship as a space of masculine homosociality and freedom. As such, they became symbols of the vanishing maritime life and community, while the bodies of albatrosses, caught and often killed by the sailors, bear witness also to the fact that the human exploitation of nature is an important part of maritime history.